2021
DOI: 10.1002/alz.12509
|View full text |Cite
|
Sign up to set email alerts
|

Black and White individuals differ in dementia prevalence, risk factors, and symptomatic presentation

Abstract: Introduction:Although dementia prevalence differs by race, it remains unclear whether cognition and neuropsychiatric symptom severity differ between Black and White individuals with dementia. Methods:Using National Alzheimer's Coordinating Center (NACC) data, we evaluated dementia prevalence in non-Hispanic Black and White participants and compared their clinicodemographic characteristics. We examined race differences in cognition, neuropsychiatric symptoms, and functional abilities in participants with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 56 publications
6
72
2
1
Order By: Relevance
“…Second, almost all participants in the study were born in Europe, which must be considered, as ethnicity is a known risk factor in different neurodegenerative conditions. 46 Third, the number of participants volunteering for CSF sampling was low in absolute numbers, thus yielding low statistical power. Furthermore, it is possible that stratification of Aβ 42/40 instead of Aβ 42 would have resulted in a more‐specific stratification of participants with Aβ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Second, almost all participants in the study were born in Europe, which must be considered, as ethnicity is a known risk factor in different neurodegenerative conditions. 46 Third, the number of participants volunteering for CSF sampling was low in absolute numbers, thus yielding low statistical power. Furthermore, it is possible that stratification of Aβ 42/40 instead of Aβ 42 would have resulted in a more‐specific stratification of participants with Aβ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in areas that benefit from sustained economic growth (e.g., "Silicon Valley"), which may form advantaged clusters and outliers, we find favorable mortality for diabetes and chronic lower respiratory disease. Likewise, we find that class and race may intersect for Alzheimer's disease, which is not only of higher prevalence among African American/Black populations and underdiagnosed as well 34 . Finally, we find that place and race intersect in the western US, with higher county whiteness as well as rates of suicide 35 and other "deaths of despair" 36 .…”
Section: Discussionmentioning
confidence: 61%
“…However, contrary to our hypothesis, we found that Black individuals were not more vulnerable to the effect of everyday discrimination in this respect. Although some research suggests that Black individuals are diagnosed with AD 1.33 to 1.50 times more often than whites ( Akushevich et al, 2020 ; Matthews et al, 2019 ; Mayeda et al, 2016 ), other research suggests that Black individuals are 30% less likely to receive a diagnosis (e.g., Lennon et al, 2021 ). We found that there were not race differences in either of these directions regarding the percentage of respondents who had AD at follow-up and that everyday discrimination did not have a stronger effect for Black respondents.…”
Section: Discussionmentioning
confidence: 99%